2005
DOI: 10.1521/suli.35.2.227.62876
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Cohort Study of Stress, Life Satisfaction, Self‐Rated Health, Insomnia, and Suicide Death in Japan

Abstract: The association between many psychosocial factors and risk of suicide was examined. A cohort was conducted over 14 years of follow up among the general population (15,597 people) in Japan. A baseline survey of psychosocial characteristics was conducted by self-administrated questionnaire. The relative risks of occasional emotional stress, difficulty maintaining sleep, and reporting unhealthy as their self-rated health are 3.2 (95% CI: 1.3, 7.6), 2.4 (95% CI: 1.3, 4.3) and 2.6 (95% CI: 1.1, 6.2), respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
78
2
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(89 citation statements)
references
References 29 publications
3
78
2
6
Order By: Relevance
“…Prolonged, excessive stress or depression are linked with thinking about suicide and attempted suicide (GoldmanMellor et al 2014); and most suicide attempts are by those who have previously thought of suicide (Bronisch and Wittchen 1994). For example, a 14-year follow-up study reported that stress and suicidal ideation were associated with action of suicidal thoughts (Fujino et al 2005). Short sleep duration may affect both psychological and physiological health conditions, with negative effects on judgment, fatigue, stress, and impulse control.…”
Section: Discussionmentioning
confidence: 99%
“…Prolonged, excessive stress or depression are linked with thinking about suicide and attempted suicide (GoldmanMellor et al 2014); and most suicide attempts are by those who have previously thought of suicide (Bronisch and Wittchen 1994). For example, a 14-year follow-up study reported that stress and suicidal ideation were associated with action of suicidal thoughts (Fujino et al 2005). Short sleep duration may affect both psychological and physiological health conditions, with negative effects on judgment, fatigue, stress, and impulse control.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 However, in recent years there has been growing evidence that sleep problems are risk factors for self-harm and suicidal behaviour and that this relationship is independent of psychiatric disorder. [8][9][10][11][12] Despite the accumulation of evidence confirming a relationship between sleep problems and self-harm in adolescents, the utility of the findings has been circumscribed because the measures of sleep have tended to be brief. As a consequence, it is not clear whether specific characteristics of sleep disturbance are more strongly associated with risk of self-harm than others.…”
mentioning
confidence: 99%
“…This link has been reported in both clinical (Ağargün and Cartwright, 2003;Bernert et al, 2005;Sabo et al, 1991) and nonclinical population-based samples (Fujino et al, 2005;Goodwin and Marusic, 2008;Turvey et al, 2002) regarding suicidal ideation, suicide attempt, and death by suicide.…”
Section: Discussionmentioning
confidence: 65%
“…Cross-sectionally, insomnia has repeatedly been linked to greater levels of suicidal ideation (Ağargün et al, 1997a;Barraclough and Pallis, 1975) even after controlling for depressive symptoms (Bernert et al, 2005(Bernert et al, , 2009Chellappa and Araújo, 2007), and suicidal behavior (Goldstein et al, 2008;Sjöström et al, 2007). Longitudinal studies (though few) provide even more compelling evidence, indicating that insomnia emerges as a significant predictor of later suicidal ideation (McCall et al, 2010) and death by suicide (Fawcett et al, 1990;Fujino et al, 2005;Turvey et al, 2002).…”
Section: Past Research On Sleep Problems and Suicidalitymentioning
confidence: 99%